Evaluation of Section Shift Converter (HTS and LTS) Catalyst Performance Based on CO Conversion Value, Pressure Drop, and ATE - Prahady Susmanto; Alya Putri Yolanda; Riska Puspitasari; Dwi Anggraini (Universitas Tribhuwana Tunggadewi Malang, 2025)
The shift converter process uses Copper-promoted iron (HTS) and Copper/Zinc (LTS) catalysts to convert syngas into hydrogen through the water-gas shift reaction. Catalytic performance evaluation was conducted by analyzing parameters such as Approach Temperature Equilibrium (ATE), pressure drop, and CO conversion. The findings indicate that in the HTS unit, CO conversion ranged from 69% to 75%, with a significant decline to 69% in the fifth data set due to reduced catalyst activity. Key contributing factors to this decrease include catalyst deactivation caused by sintering and poisoning. Within the LTS unit, CO conversion reached a peak value of 94.08% following the catalyst replacement in January 2024. This observed pressure drop also significantly affected catalyst efficiency, as increased pressure drop reduced the contact time between reactant gases and the catalyst, decreasing optimal CO conversion efficiency. ATE analysis showed that the reaction did not always reach the expected thermodynamic equilibrium, particularly in the HTS unit, where ATE values exceeding design specifications indicated inefficient reaction performance. Catalyst efficiency in the shift converter is significantly influenced by catalyst lifespan, pressure drop, and various operational factors, thus requiring routine catalyst replacement to maintain optimal reactor performance.